ENHANCING INTRINSIC MOTIVATION AND LISTENING SKILLS THROUGH INTEGRATING AUTHENTIC LEARNING MATERIALS - Husnawati, Nurul; Puspitasari, Maya; Yundayani, Audi (University of Kuningan, 2024)
Authentic learning materials (ALM) are recognized for providing meaningful and engaging educational experiences. However, there is a lack of extensive research examining the relationship between authentic learning materials, students’ intrinsic motivation, and their listening skills. This study addresses this gap by employing a quantitative method through the distribution of a 35-item Likert scale questionnaire to junior high school students in Batam. The questionnaire aimed to assess students’ attitudes and perceptions regarding the use of authentic materials in their English classes. The results from 30 students indicated that authentic learning materials positively influence student engagement, intrinsic motivation, and cultural awareness. These materials were found to enhance students' interest and participation in learning activities by making the content more relatable and applicable to real-life situations. The study also highlighted some challenges, such as difficulties in comprehension and issues with classroom dynamics, which could impact the overall effectiveness of these materials. Despite these challenges, the data suggest that authentic learning materials effectively bridge the gap between classroom learning and real-world language use. This connection fosters a sense of achievement and satisfaction among students, as they can see the practical application of their language skills. Thus, incorporating authentic materials into the curriculum can provide significant benefits, enhancing the overall learning experience and motivation of students in the English classroom.